The effectiveness of policy makers during uncertain environment: Evidence from a set of emerging market economies - Soon, Siew Voon; Baharumshah, Ahmad Zubaidi (2018)
This paper ascertain the effect of changes in the domestic interest rate on exchange rate movement, using monthly data from a set of emerging market economies. The central banks are responding to the exchange rate movements in addition to the other core variables, namely, inflation gap and the output gap. In addition, countries with a high degree of financial openness are more responsive to the movement in the exchange rate, but this has weakened the effectiveness of disinflationary policy. Policy makers should behave pre-emptive and necessitate the exchange rate adjustment as alternative policy choice, in the calculus of formulating policy rule.